Vitamin D and Hair: A review of current methods and validation of a quantitation method to measure 25(OH)D3 from hair - Maher, Padraig Edward (Trinity College Dublin. School of Medicine. Discipline of Public Health & Primary Care, 2025)
Introduction: Hair has emerged as a promising matrix for assessing endogenous steroid hormone levels, yet its potential for the quantitation of vitamin D remains unexploited. Vitamin D status is typically assessed by measuring the circulating concentration of 25-hydroxyvitamin D3 (25(OH)D3) from a blood sample. 25(OH)D3 is the most abundant, 'storage' form of vitamin D3 and serves as the biomarker for vitamin D status. This study aimed to develop and validate a liquid chromatography mass spectrometry (LC-MS/MS) method for measuring 25(OH)D3 in human and animal hair. Method: A systematic review was conducted on 180 studies which describe endogenous steroid hormone analysis (cortisol, testosterone, androstenedione, dehydroepiandrosterone sulfate, 17-hydroxyprogesterone and vitamin D) in hair of humans and animals. Current methodologies employed in hair analysis were identified, to inform method of 25(OH)D3 assessment. The validation of a method to measure 25(OH)D3 in hair employed five validation parameters to evaluate suitability. A standard calibration curve to check linearity, limit of quantitation and limit of detection of the assay, accuracy, precision and comparison between hair preparation and effect on results. This method was then be applied to human and animal hair samples. Results: Review findings suggest that while hair is a viable matrix for steroid measurement, further refinement is needed before it can be routinely applied in clinical settings as clinical requirements are more stringent. Guidelines for steroid testing in hair should standardise practices for sample collection, storage, pre-treatment, and analysis, alongside validation protocols, all of which were found to be varied among studies. The validation of the proposed method for quantifying 25(OH)D3 in hair was completed and provided a highly sensitive, selective and reliable method. This validated method was used for hair samples from human, bovine, chimpanzee and lemurs. The difference in levels from human (Mean; 146 pg/mg) to animal (Mean; 1585 pg/mg) varied largely. Animals are routinely supplemented when in captivity and do not seem to be affected by toxicity at the same levels as humans. Conclusion: The future of hair analysis of 25(OH)D3 and other endogenous steroid hormones could be a useful tool in clinical and research settings. Further testing with larger sample size of varying age, sex and hair type is required in subsequent studies.
APPROVED